KAJIAN AGROFORESTRI DI BAWAH TEGAKAN PINUS UNTUK MENINGKATKAN PRODUKTIVITAS LAHAN DAN KESEJAHTERAAN PETANI STUDI KASUS : DI DESA PUJONKIDUL KECAMATAN PUJON KABUPATEN MALANG - Triwanto, Joko; Mutaqqin, Tataq (Universitas Muhammadiyah Palembang, 2018)
Agroforestry is a promising method for increasing sustainable land use, because of the gap in understanding the perceptions of land users by considering the local and global environment (Brandt et al., 2012). It was also explained by Araujo et al. (2012) that agroforestry systems are a form of sustainable land use that combines trees and shrubs with plants and livestock in ways that increase and diversify agriculture and production forests. This study aims to study agroforestry in the village of Pujonkidul which can increase land productivity, so that community welfare increases. The data taken in this study are primary data and secondary data collection methods, namely field observations, interviews, questionnaires and literature studies. Descriptive qualitative analysis results, agroforestry studies in the village of RPH Pujonkidul BKPH Pujon Pujonkidul beneficial and improve the welfare of the community, because of high land productivity. The highest B / C ratio is carrots = 8.6> 1., cabbage = 9.2> 1., mustard = 6.6> 1). Pine stands in agroforestry, with an average diameter of 0.19-0.32 meters, a height of 7 to ± 11 meters, a volume of 0.27 to 0.85 m3 with a wide canopy of 1 to 17 meters. Agroforestri sebagai metode yang menjanjikan untuk meningkatkan penggunaan lahan berkelanjutan, karena kesenjangan dalam memahami persepsi pengguna lahan dengan mempertimbangkan lingkungan lokal dan global (Brandt et al., 2012). Dijelaskan juga oleh Araujo et al. (2012) bahwa sistem wanatani adalah bentuk penggunaan lahan berkelanjutan yang menggabungkan pohon dan semak dengan tanaman dan ternak dengan cara yang meningkatkan dan diversifikasi pertanian dan hutan produksi. Penelitian ini bertujuan untuk mengaji agroforestry di desa Pujonkidul yang dapat meningkatkan produktivitas lahan, sehingga kesejahteraan masyarakat meningkat. Data yang diambil dalam penelitian ini adalah data primer dan metode pengumpulan data sekunder, yaitu observasi lapangan, wawancara, kuesioner dan studi pustaka. Hasil analisis deskriptif kualitatif, kajian agroforestry di desa RPH Pujonkidul BKPH Pujon Pujonkidul menguntungkan dan meningkatkan kesejahteraan masyarakat, karena produktivitas lahan tinggi. B / C rasio tanaman paling tinggi yaitu wortel = 8,6> 1., kubis = 9,2> 1., mustar = 6,6> 1). Pinus berdiri di agroforestri, diameter rata-rata 0,19-0,32 meter, tinggi 7 hingga ± 11 meter, volume 0,27 hingga 0,85 m3 dengan kanopi lebar 1 hingga 17 meter.